Blatter‐Radical‐Grafted Mesoporous Silica as Prospective Nanoplatform for Spin Manipulation at Ambient Conditions. (9th March 2021) - Poryvaev, Artem S.; Gjuzi, Eva; Polyukhov, Daniil M.; Hoffmann, Frank; Fröba, Michael; Fedin, Matvey V.
Abstract: Quantum computing and quantum information processing (QC/QIP) crucially depend on the availability of suitable quantum bits (qubits) and methods of their manipulation. Most qubit candidates known to date are not applicable at ambient conditions. Herein, we propose radical‐grafted mesoporous silica as a versatile and prospective nanoplatform for spin‐based QC/QIP. Extremely stable Blatter‐type organic radicals are used, whose electron spin decoherence time is profoundly long even at room temperature (up to Tm ≈2.3 μs), thus allowing efficient spin manipulation by microwave pulses. The mesoporous structure of such composites is nuclear‐spin free and provides additional opportunities of embedding guest molecules into the channels. Robustness and tunability of these materials promotes them as highly promising nanoplatforms for future QC/QIP developments. Abstract : Extremely stable Blatter's type organic radicals grafted into the mesoporous silica show advanced relaxation properties at room temperature. Electron spin decoherence time exceeds that in many other qubit candidates, allowing efficient spin manipulation at ambient conditions. The tuneable multifunctional nature of such composite materials promotes them as promising nanoplatforms for developing new spin‐based quantum bits.